Effects of propofol in lipid-based emulsion and in microemulsion on the incidence of endothelial lesion in rabbits - Paço, Cristian Durço [UNESP]; Vane, Matheus Fachini; Andrade, Rafael Bicarato De [UNESP]; Domingues, Maria Aparecida Custódio [UNESP]; Carvalho, Lidia Raquel De [UNESP]; Santos, Daniela Carvalho Dos [UNESP]; Takahira, Regina Kiomi [UNESP]; Módolo, Norma Sueli Pinheiro [UNESP]; Vane, Luiz Antonio [UNESP] (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2013)
PURPOSE: To compare the incidence of endothelial injury after single-dose or continuous propofol infusion in conventional lipid-based emulsion (LE) versus microemulsion (ME). METHODS: Forty-two rabbits (2.5-4.5 Kg) were randomly allocated into seven groups of six animals each: SHAM- surgical treatment alone; Bolus Control Group - 3 mL-intravenous (IV) bolus of saline; Continuous Infusion Control Group - 3 mL- IV bolus of saline followed by a continuous infusion of 0.2 ml/kg/min for 60 min; Bolus LE Propofol Group - IV bolus of LE propofol (3 mg/kg); Bolus ME Propofol Group - IV ME propofol bolus (3 mg/kg); Continuous LE Propofol Group - IV LE propofol bolus (3 mg/kg) followed by a continuous infusion of 0.2 ml/kg/min for 60 min; Continuous ME Propofol Group - IV ME propofol bolus (3 mg/kg) followed by a continuous infusion of 0.2 ml/kg/min for 60 min. RESULTS: There were no statistically significant differences between the studied groups in blood pressure, in central venous pressure and in the biochemical profile. No significant differences were found in inflammatory mediators and in tissue analysis between the two emulsions. CONCLUSION: Microemulsion and lipid-based emulsion propofol had similar inflammatory, biochemical and microscopy profiles. Thus, microemulsion propofol can be used as an alternative to lipid-based emulsion propofol.
Keywords: Anesthetics; Intravenous; Propofol; Solvents; Inflammation; Microscopy; Rabitts